DEVELOPMENT OF WEB-BASED LEARNING FOR INFORMATICS SUBJECTS FOR CLASS X OF SMKN 2 TULUNGAGUNG IN THE 2024/2025 ACADEMIC YEAR - Sultan Ramadhon, Mohammad Mahandika; Haris, Abdul (CV. AKIRA JAVA BULU, 2025)
Education is currently developing rapidly due to the digital era. The use of traditional learning methods, which require students to meet face-to-face with teachers and rely solely on textbooks, is now considered less attractive to students. Learning media has also evolved along with technological advancements. Learning media can be used as a tool to support the teaching and learning process. With the presence of learning media, students become more motivated and enthusiastic in participating in lessons, which can increase their learning interest. Learning media is a platform or tool used by teachers in the teaching and learning process. This research focuses on the development of web-based learning media, which was created using Bootstrap, Visual Studio Code, and Quizizz as the evaluation tool. This research aims to develop web-based learning media and measure its feasibility. The research model used is ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Based on the results, the media expert validation achieved a score of 95.45%, categorized as Very Good, while the material expert validation obtained a score of 87.5%, also categorized as Very Good. The small group trial produced a score of 91.42%, which falls into the Very Good category, and the large group trial achieved a score of 92.93%, also categorized as Very Good. Based on these results, it can be concluded that the development of web-based learning media for the Informatics subject in Grade X at SMKN 2 Tulungagung is highly feasible for use.